KONSEP DAN PELAKSANAAN KONSELING NARRATIVE: STUDI KEPUSTAKAAN - Hoirot, Izza Muassisul; Purwoko, Budi; Habsyi, Bakhrudin All (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
Narrative Counseling is one of the Post Modern counseling approaches that refers to the ideas and practices of Michael White and David Epston. is a Post Modern counseling approach that focuses on the human capacity to think creatively and imaginatively. The counselee is the main interpreter of their own life experiences and is able to rewrite their narratives according to future expectations. In the scope of education / school, narrative counseling can be applied to help overcome various counselee problems. Both in the personal, social, learning and career fields. With the use of social media or other media that are adjusted to the needs of the counselee. In its implementation, Narrative counseling can also be combined with other counseling approaches